Status and the True Believer: The Impact of Psychological Contracts on Social Status Attributions of Friendship and Influence - Bingham, John B.; Oldroyd, James B.; Thompson, Jeffery A.; Bednar, Jeffrey S.; Bunderson, J. Stuart (Organization Science, 2014)
This article examines how the fulfillment of obligations viewed as essential to an individual’s relationship with his or her employer (i.e., the psychological contract) affects attributions of friendship and influence within the organization. Drawing on social exchange theory and self-categorization theory, we hypothesize that individuals who fulfill relational obligations will receive more friendship nominations from others in the organization, whereas individuals who fulfill ideological obligations will receive more influence nominations. In contrast, we hypothesize that those who fulfill transactional obligations will receive fewer friendship and influence nominations. We also predict that individuals who hold similar beliefs about their relationship with the organization will be more likely to nominate similar coworkers as friends or as influential in the organization, and that ideological contract similarity may provide a more compelling rationale for influence nomination than transactional or relational contract similarity. We tested our framework in two samples and find support for these general hypotheses. Our findings suggest that positions of status and influence in ideologically oriented organizations may accrue to “true believers,” i.e., those whose contracts with the organization are construed in ideological terms. Accordingly, this study has important implications for research on psychological contracts and social influence.